Integrating Comprehensive Mathematics Instruction into Google Classroom: Effects on Students’ Mathematical Critical Thinking and Self-Efficacy - Nita Delima; Ismi Jamesti Sayekti; Nurhayati Nurhayati; Endang Irawan Supriyadi; Mazlan Che Soh (FKIP Universitas Lampung, 2026)
Indonesian students’ mathematics performance remains below the OECD average, particularly on items requiring reasoning, interpretation of data, and problem-solving in real-world contexts. Although PISA outcomes are influenced by multiple factors, including curriculum alignment, learning opportunities, and socioeconomic conditions, prior studies indicate that students’ difficulties with non-routine, reasoning-based tasks reflect limitations in higher-order mathematical thinking. In this context, strengthening students’ mathematical critical thinking remains an urgent instructional challenge. This study aimed to determine whether students’ mathematical critical thinking skills improved more significantly after using a Google Classroom-based Comprehensive Mathematics Instruction (CMI) model than after regular learning. Additionally, this research examined changes in students’ mathematics self-efficacy before and after the intervention and explored the relationship between mathematical critical thinking skills and mathematics self-efficacy. A quasi-experimental nonequivalent control group design was employed. The population consisted of all tenth-grade students at SMAN 1 Jalancagak, with a purposive sample of 70 students drawn from two classes (X-10 and X-9). Data were collected using a mathematical critical thinking test and a mathematics self-efficacy questionnaire. The results show that students using the Google Classroom-based CMI model achieved significantly greater improvements in mathematical critical thinking skills than those in standard learning. Moreover, students’ mathematics self-efficacy increased significantly following implementation of the model. The analysis also found a statistically significant, though modest, relationship between mathematical critical thinking skills and mathematics self-efficacy. These results indicate that combining structured cognitive instruction with digital learning environments can enhance students’ mathematical critical thinking and mathematics self-efficacy, while recognising that broader contextual factors influence their mathematics development achievement. Keywords: CMI model, google classroom-based CMI model, google classroom, mathematical critical thinking skills, mathematics self-efficacy.